Aksesibilitas Mahasiswa Kesehatan dan Mahasiswa Non Kesehatan Strata S-1 Universitas Airlangga terhadap Program Jaminan Kesehatan Nasional - Ulfia Hazna Safira (Indonesian Journal of Health Administration (Jurnal Administrasi Kesehatan Indonesia), 2018)
The participants of National Health Security in October 2016 still reached 66,11% of population. Society's and students' knowledge about the benefits and use of National Health Security was still low. The lack of knowledge, service use, and community participation showed the lack of accessibility of the National Health Security program. Students as agents of change are expected to make National Health Security successful. The objective of this research was to analyze the differences of health student’s accessibility and non-health student’s accessibility to National Health Security program. The method of this research was online questionnaires with an analytic type of research. The study used observational  and cross sectional design. The results showed there were differences of accessibility between health students and non-health students based on knowledge, proximity of health facility that accepts National Health Security, perception of the importance of National Health Security, National Health Security participants, utilization of National Health Security, accessible information of National Health Security, affordability of National Health Security, and satisfaction of National Health Security. Meanwhile, health students' and non-health students' accessibility did not have differences on information access aspect, accommodation availability, and perception of the accuracy of National Health Security program.Keywords: accessibility, national health security, students